Prevalence of Refractive Errors in a Brazilian Population: The Botucatu Eye Study - Schellini, Silvana Artioli [UNESP]; Durkin, Shane R.; Hoyama, Erika [UNESP]; Hirai, Flavio [UNESP]; Cordeiro, Ricardo [UNESP]; Casson, Robert J.; Selva, Dinesh; Padovani, Carlos Roberto [UNESP] (Taylor & Francis Inc, 2009)
Purpose: To determine the prevalence and demographic associations of refractive error in Botucatu, Brazil. Methods: A population-based, cross-sectional prevalence study was conducted, which involved random, household cluster sampling of an urban Brazilian population in Botucatu. There were 3000 individuals aged 1 to 91 years (mean 38.3) who were eligible to participate in the study. Refractive error measurements were obtained by objective refraction. Results: Objective refractive error examinations were performed on 2454 residents within this sample (81.8% of eligible participants). The mean age was 38 years (standard deviation (SD) 20.8 years, Range 1 to 91) and females comprised 57.5% of the study population. Myopia (spherical equivalent (SE) < -0.5 dropters (D)) was most prevalent among those aged 30-39 years (29.7%; 95% confidence interval (CI) 24.8-35.1) and least prevalent among children under 10 years (3.8%; 95% confidence interval (CI) 1.6-7.3). Conversely hypermetropia (SE > 0.5D) was most prevalent among participants under 10 years (86.9%; 95% CI 81.6-91.1) and least prevalent in the fourth decade (32.5%; 95% CI 28.2-37.0). Participants aged 70 years or older bore the largest burden of astigmatism (cylinder at least -0.5D) and anisometropia (difference in SE of > 0.5D) with a prevalence of 71.7% (95% CI 64.8-78.0) 55.0% (95% CI 47.6-62.2) respectively. Myopia and hypermetropia were significantly associated with age in a bimodal manner (P < 0.001), whereas anisometropia and astigmatism increased in line with age (P < 0.001). Multivariate modeling confirmed age-related risk factors for refractive error and revealed several gender, occupation and ethnic-related risk factors. Conclusions: These results represent previously unreported data on refractive error within this Brazilian population. They signal a need to continue to screen for refractive error within this population and to ensure that people have adequate access to optical correction.
Keywords: anisometropia; Astigmatism; Brazil; hypermetropia; myopia; prevalence; refractive error; risk factors